Identification of mucin degraders of the human gut microbiota - Raimondi, Stefano (Sci Rep, 2021)
Mucins are large glycoproteins consisting of approximately 80% of hetero-oligosaccharides. Gut mucin degraders of healthy subjects were investigated, through a culture dependent and independent approach. The faeces of five healthy adults were subjected to three steps of anaerobic enrichment in a medium with sole mucins as carbon and nitrogen sources. The bacterial community was compared before and after the enrichment by 16S rRNA gene profiling. Bacteria capable of fermenting sugars, such as Anaerotruncus, Holdemania, and Enterococcaceae likely took advantage of the carbohydrate chains. Escherichia coli and Enterobacteriaceae, Peptococcales, the Coriobacteriale Eggerthella, and a variety of Clostridia such as Oscillospiraceae, Anaerotruncus, and Lachnoclostridium, significantly increased and likely participated to the degradation of the protein backbone of mucin. The affinity of E. coli and Enterobacteriaceae for mucin may facilitate the access to the gut mucosa, promoting gut barrier damage and triggering systemic inflammatory responses. Only three species of strict anaerobes able to grow on mucin were isolated from the enrichments of five different microbiota: Clostridium disporicum, Clostridium tertium, and Paraclostridium benzoelyticum. The limited number of species isolated confirms that in the gut the degradation of these glycoproteins results from cooperation and cross-feeding among several species exhibiting different metabolic capabilities.